City of Darkness, City of Light Emigré Filmmakers in Paris 1929-1939 - Phillips, Alastair (Film Culture in Transition, 2003)
This title is the first ever book-length study of the cinematic representation of Paris in the films of German emigré filmmakers, who found there a first refuge from Hitler. In coming to Paris - the privileged site in terms of production, exhibition as well as the cinematic imaginary of French film culture - these experienced film professionals encountered also a darker side: hostility toward Germans, anti-Semitism, as well as boycotts from French industry personnel, afraid of losing their jobs to foreigners. The book juxtaposes the cinematic portrayal of Paris in the films of Robert Siodmak, Billy Wilder, Fritz Lang, Max Ophüls, Anatol Litvak and others with the wider social and cultural debates about the city in the cinema.